Polypropylene Midurethral Tapes Do Not Have Similar Biologic and Biomechanical Performance in the Rat - Abi Nader, Khalil (2007)
Objectives To evaluate the biomechanical properties and histologic changes of different commercially available polypropylene midurethral tapes (MUTs) after implantation in the rat. Methods Pieces of Advantage®, intravaginal slingplasty (IVS), suprapubic arch sling (SPARC™), and tension-free vaginal tape (TVT) were implanted over the rectus fascia of rats, with six rats serving as controls. On retrieval 24 wk later, the degree of adherence and sample measurements were recorded. Biomechanical testing of the retrieved samples was performed using the uniaxial loading method. Histologic evaluation of the samples under light microscopy included the following parameters: inflammatory infiltrate, fibrosis, mast cell presence, muscular infiltration, and collagen filling of the mesh. Results No mesh extrusion or infection was encountered. The biomechanical and histologic results were consistent within each group. TVT displayed peculiar adherence characteristics not found among the other brands. No statistically significant difference were found in mean peak load and extension at peak load among the four tested brands. Stiffness of TVT was significantly lower than that of each of the other three brands. Stiffness of Advantage was significantly higher than that of SPARC. The histologic findings differed from one MUT brand to another. By grading certain histologic parameters, an untested model to assign a score for biocompatibility potential in the rat, to different MUTs, was developed. Conclusions Commercially available polypropylene MUTs display different biologic and biomechanical properties in the rat.